Implementation of Work Discipline and Application of Employee Sanctions In PD. BPR Rokan Hulu - Sosiady, Mulia (Basecamp Economics PubMed, 2024)
This study was conducted at BPR PD Rokan Hulu, utilizing a qualitative descriptive analysis based on interviews. The primary objective was to investigate the disciplinary practices and the application of punishment among employees within the institution. The findings reveal that to enhance disciplinary diversity, BPR PD Rokan Hulu has established robust regulations and enforced sanctions effectively. This initiative demonstrates BPR PD Rokan Hulu's commitment to promoting diversity through structured training programs and the implementation of punitive measures. Despite these efforts, the study identified that there are still instances of indiscipline among some employees. Specific violations observed include habitual tardiness, absenteeism without prior approval from supervisors, and unexplained departures during official work hours. These actions not only contravene the company's established regulations but also undermine the overall disciplinary framework intended to foster a productive and efficient work environment. The research highlights the significance of continuous monitoring and reinforcement of disciplinary measures to ensure adherence to organizational norms and standards. Furthermore, it suggests that while the implementation of rules and sanctions is vital, BPR PD Rokan Hulu could benefit from exploring additional strategies to address the root causes of indiscipline. This could include more personalized training sessions, enhanced communication channels between employees and management, and the development of a more inclusive company culture that encourages respect for regulations. In conclusion, while BPR PD Rokan Hulu has made commendable strides in enforcing discipline and applying necessary sanctions, there is room for improvement. Addressing the lingering issues of employee indiscipline requires a multifaceted approach that not only penalizes non-compliance but also actively fosters an organizational culture that values punctuality, responsibility, and adherence to established guidelines.This study was conducted at BPR PD Rokan Hulu, utilizing a qualitative descriptive analysis based on interviews. The primary objective was to investigate the disciplinary practices and the application of punishment among employees within the institution. The findings reveal that to enhance disciplinary diversity, BPR PD Rokan Hulu has established robust regulations and enforced sanctions effectively. This initiative demonstrates BPR PD Rokan Hulu's commitment to promoting diversity through structured training programs and the implementation of punitive measures. Despite these efforts, the study identified that there are still instances of indiscipline among some employees. Specific violations observed include habitual tardiness, absenteeism without prior approval from supervisors, and unexplained departures during official work hours. These actions not only contravene the company's established regulations but also undermine the overall disciplinary framework intended to foster a productive and efficient work environment. The research highlights the significance of continuous monitoring and reinforcement of disciplinary measures to ensure adherence to organizational norms and standards. Furthermore, it suggests that while the implementation of rules and sanctions is vital, BPR PD Rokan Hulu could benefit from exploring additional strategies to address the root causes of indiscipline. This could include more personalized training sessions, enhanced communication channels between employees and management, and the development of a more inclusive company culture that encourages respect for regulations. In conclusion, while BPR PD Rokan Hulu has made commendable strides in enforcing discipline and applying necessary sanctions, there is room for improvement. Addressing the lingering issues of employee indiscipline requires a multifaceted approach that not only penalizes non-compliance but also actively fosters an organizational culture that values punctuality, responsibility, and adherence to established guidelines.